2013
DOI: 10.1055/s-0033-1345179
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Influences Predict Recovery Following Exercise Induced Shoulder Pain

Abstract: Predicting recovery following muscle injury can be difficult because it involves consideration of multiple factors. Our objective was to determine if psychological factors, sex, and peak pain and disability ratings could be predictive of delayed recovery following induced muscle injury. Healthy untrained volunteers (n=126; M:F 51:75) underwent a concentric/eccentric isokinetic exercise protocol on their dominant shoulder to induce fatigue, with individuals who reported pain (>0/10) at 96 h being classified as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 11 publications
(16 reference statements)
0
19
0
Order By: Relevance
“…Parr et al confirmed these findings, demonstrating that patients with higher pain-related fear scores and pain catastrophizing had higher reported levels of pain, longer duration of pain, and worse recovery after standardized acute muscle injury. 23 This indicates that the relationship of pain scores and SANE scores and emotional distress, as demonstrated in this study, may not be a truly linear relationship but is a "twoway street. "…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Parr et al confirmed these findings, demonstrating that patients with higher pain-related fear scores and pain catastrophizing had higher reported levels of pain, longer duration of pain, and worse recovery after standardized acute muscle injury. 23 This indicates that the relationship of pain scores and SANE scores and emotional distress, as demonstrated in this study, may not be a truly linear relationship but is a "twoway street. "…”
Section: Discussionmentioning
confidence: 66%
“…Previous authors have catalogued that a number of psychosocial variables have an effect on patients' perceptions of pain and function. 6,10,11,13,17,23,24 This knowledge as well as extensive research by the WORC group in creating the WORC score led them to create a specific subgroup devoted to emotional parameters, the WORC emotion score. Despite evidence of the importance of the emotional state of the patient with a rotator cuff tear, no study has directly assessed which factors correlate with a better or worse WORC emotion score.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exercise continued until participants could only generate 50% of their original shoulder external rotation maximum voluntary isometric contraction (MVIC). Previous studies have used 50% MVIC as a level indicating fatigue in the shoulder; furthermore, our group has successfully used this protocol in prior studies to induce DOMS, specifically in the shoulder …”
Section: Methodsmentioning
confidence: 99%
“…The isokinetic exercise protocol was based on other studies 19,22,23 using similar equipment and had been previously used in our laboratory. [24][25][26] Participants were placed in the Kin-Com in an upright seated position with the torso strapped into the chair to isolate movement of the dominant shoulder. Two straps crossed the participant's torso and an additional strap crossed the lap to limit all movement per the manufacturer's recommendations.…”
Section: Shoulder-fatigue Protocolmentioning
confidence: 99%